POLA DISTRIBUSI PASIEN KOLELITIASIS DI RSU DR. SOEDARSO PONTIANAK PERIODE JANUARI 2010 PERIODE JANUARI 2010-DESEMBER 2011 - ., Krisantus Hendrik (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background:Gallstone disease known as cholelithiasis is one of the mostcommon digestive surgical disorder in the United States and in developedcountry in general. Individual with symptomatic gallstones may experiencevarious gartrointestinal symptoms and are also at risk of developing acutecholecystitis and other complications although the majority of individualswith gallstones remain asymptomatic.Objective: This research was aimed to know the distribution ofcholelithiasis patients according to age, sex, main symptom, additionalsymptom, and complication in dr. Soedarso General Hospital Pontianakduring the period of January 2010-December 2011.Method: This research was a descriptive study with cross-sectionalapproach which was conducted by using secondary data from medicalrecords.Result: Among a total of 99 cholelithiasis patients, 63 (63,6%) werefemales and 36 (36,4%) were males with ratio (F:M) was 1,75:1. Most ofpatients were in age group of 41-48 years (23,2%) with femalepredominance (ratio F:M=1,6:1). The most common main symptom wasupper right quadrant pain (55,6%) and followed by epigastrium pain(44,4%). The most common additional symptom was nausea and/orvomitting (76,8%). There were 47 (47,5%) patients had complication; 36(36,4%) had cholecystitis, 9 (9,1%) had jaundice, and 2 (2,0%) had acutepancreatitis.Conclusion: The most common cholelithiasis patients were female and inage group of 41-48 years. The most common main symptom was upperright quadrant pain. The most common additional symptom was nauseaand/or vomitting. The most common complication was acute cholecystitis.Keyword: cholelithiasis, age, sex, main symptom, additional symptom,complication, dr. Soedarso General Hospital Pontianak